Evidenzbasierte antithrombotische Therapie der peripheren arteriellen Verschlusskrankheit (PAVK) - Behrendt, Christian Alexander; Larena-Avellaneda, Axel; Gombert, Alexander; Rother, Ulrich (Gefässchirurgie, 2023)
The evidence-based guideline-compliant antithrombotic treatment of patients with peripheral arterial occlusive disease (PAOD) has for a long time been a challenge in the routine clinical practice of vascular specialists. For the first time in 2023 clinical practice guidelines of the European Society for Vascular Surgery (ESVS) that explicitly deal with the antithrombotic treatment of patients with vascular diseases are expected. Many decisions and guideline recommendations have been based on studies from other medical specialties as no suitable evidence base exists. Most recently, innovative studies were published that introduced more knowledge but also new challenges for healthcare professionals. This article provides an overview of the current study situation and its relevance in clinical practice. Thereby, it explicitly discusses the different treatment options (conservative, endovascular, open surgery) and the difficult balance between efficacy and safety of antithrombotic drugs. The advantages and disadvantages of composite endpoints of current studies as well as the inherent selection bias and risk for major bleeding events are meticulously discussed. Simultaneously, the current treatment reality including the prescription practice is also presented.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Antithrombotic treatment; Guideline recommendations; Study situation; Treatment options; Treatment reality